Animal Models of Diabetic Retinopathy: Summary and Comparison - Angela Ka Wai Lai; Amy C. Y. Lo (Journal of Diabetes Research)
Diabetic retinopathy (DR) is a microvascular complication associated with chronic exposure to hyperglycemia and is a major cause of blindness worldwide. Although clinical assessment and retinal autopsy of diabetic patients provide information on the features and progression of DR, its underlying pathophysiological mechanism cannot be deduced. In order to have a better understanding of the development of DR at the molecular and cellular levels, a variety of animal models have been developed. They include pharmacological induction of hyperglycemia and spontaneous diabetic rodents as well as models of angiogenesis without diabetes (to compensate for the absence of proliferative DR symptoms). In this review, we summarize the existing protocols to induce diabetes using STZ. We also describe and compare the pathological presentations, in both morphological and functional aspects, of the currently available DR animal models. The advantages and disadvantages of using different animals, ranging from zebrafish, rodents to other higher-order mammals, are also discussed. Until now, there is no single model that displays all the clinical features of DR as seen in human. Yet, with the understanding of the pathological findings in these animal models, researchers can select the most suitable models for mechanistic studies or drug screening.